Hukum Tawassul Menurut Mazhab Syafi’i - Azhar Azhar; Muhammad Shaleh; Muhammad Ramadhan (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2020)
The Law of Tawassul According to the Shafi'i School (Case Study of the An-Naqsabandiyah Babussalam Besilam Order). This research is included in the qualitative research model, meaning that the data used in this study is qualitative data (data that does not consist of numbers) in the form of verbal messages, dialogues and writings which are the results of research through observation, interviews and documentation. Describe the practice of tawassul to the grave of Sheikh Abdul Wahab Rokan in Babussalam Besilam Village. The practice of Tawassul on his grave is full of problems, because the essence of tawasul is not asking for prayer to pious people who have died, because the true essence of tawasul is asking for prayer to pious people who are still alive. tawasul to people who have died. Explaining the law of tawasul in the graves of scholars according to the Shafi'i school. There are four kinds of understanding of the hadith of tawassul according to the Shafi'i school which were put forward by the author of the book and Mr. a) relying on Asmaul Husna, b) relying on righteous deeds; c) rely on living pious people; d) rely on godly people who have died. Keywords: Tawassul, Shafi'i Madhhab, Madhab